Malawi stories of change in nutrition: Funding for nutrition - Nyirongo, Godwin; Mangwele, Chiya; Bagnall-Oakeley, Hugh; Northcote, Callum; Chalemera, Jacqueline; Nowa, Mphatso; Lupafaya, Phindile; Roschnik, Natalie; Bhaiji, Rashida; Museka Saidi, Tendai; Mhango, Brian (Institute of Development Studies, 2022)
Malawi has strong policies and frameworks for nutrition but insufficient funding to implement them. Analyses of government budgets at national level and in 10 districts from financial years 2016/17 to 2022/23, found that domestic budget allocations for nutrition are still well below the 5% of national budget target set by the government. National budget allocations ranged between 0.5% to 3.7% depending on the year. At district level, they ranged from 0.2% to 1.6%, with only one district, in one financial year, exceeding the 1.5% target for district level nutrition budget allocations. Over 95% of nutrition activities in Malawi are currently funded by external donors. The absence of sufficient, consistent and dedicated domestic budget for nutrition at national and district level, means nutrition policies and plans will continue to be driven by, and dependent on, externally funded pilot-scale projects without national reach or ownership. Budget tracking is essential, as it provides data, which all actors can use to hold government to account on their commitments and funding targets.